PEMBELAJARAN BERNYANYI PADA MATA PELAJARAN SENI BUDAYA DI SMA NEGERI 3 KOTA SOLOK - Hanafi Riska; Jagar Lumbantoruan (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe the Implementation of Singing Learning in Cultural Arts subjects at SMA Negeri 3 Kota Solok. Type of the research was qualitative research with descriptive analysis method. The object of research was teachers and 11th grade students of MIA 2. The main instrument in the research was the researcher and researcher was assisted with supporting instruments such as stationery and photo cameras. Data collection was done through observation, interviews, documentation and literature review. The steps taken in analyzing data were collecting data, identifying data, classifying data and describing data. The results showed that singing learning activities at SMA Negeri 3 Kota Solok ran smoothly but had not yet reached the KKM standard. It is caused by there were still many students who had not mastered intonation, articulation, frequency, breathing, posture, and expression. Thus, it could be concluded that students’s singing ability at SMA Negeri 3 Solok especially clss XI MIA 2 was not significantly improved since the students’ participation was not yet maximal. Keywords: Learning, Singing, Art and Culture